Artificial intelligence, complementary assets and productivity: Evidence from French firms - Flavio Calvino; Luca Fontanelli (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2023)
In this work we characterise French firms using artificial intelligence (AI) and explore the link between AI use and productivity. We relevantly distinguish AI users that source AI from external providers (AI buyers) from those developing their own AI systems (AI developers). AI buyers tend to be larger than other firms, while AI developers are also younger. The share of firms using AI is highest in the ICT sector, which exhibits a particularly high share of developers. Complementary assets, including skills, digital capabilities and infrastructure, play a key role for AI use, with AI buyers and developers leveraging different types of human capital. Overall, AI users tend to be more productive, however this appears largely related to the self-selection of more productive and digital-intensive firms into AI use. This is not the case for AI developers, for which the positive link between AI use and productivity remains evident beyond selection, suggesting a positive effect of AI on their productivity.
Keywords: D20; J24; O14; O33; 330; Technology Diffusion; Artificial Intelligence; Digitalisation; Productivity